A case report of an extranodal NK/T-cell lymphoma nasal type, occurring primarily in eyes with masquerade syndrome. Issue 11 (March 2019) - Zhang, Feng; Duan, Xuanchu; Liu, Ke
Abstract: Rationale: Extranodal natural killer T-cell lymphoma nasal type (ENKL) is an extremely rare tumor with a very low survival rate. In recent decades, only a few ENKL cases have been published. Presenting a special ENKL case lead the authors to emphasize the primary features of ENKL in early diagnosis and therapy. Here we report an unusual ENKL case which was initially found in the eyes and presented as masqueraded uveitis Patient concerns: A 55 years old female, with vision loss in the right eye for approximately 6 months, and vision blurry, redness and pain in the left eye for 2 weeks, was referred to our hospital. Diagnosis: Clinical examinations and images demonstrated bilateral anterior uveitis, retinal and choroidal detachment, and secondary glaucoma. After 3 months, the patient began to present a sore throat, fever, and headaches. The computed tomography (CT) and magnetic resonance imaging (MRI) of her skull demonstrated nothing positive. One month later, a neoplasm was found in her nasopharynx and tonsil, which was confirmed, by histopathology, as ENKL Interventions: This patient was prescribed with steroid for 3 months because of the first diagnosis by the ophthalmologist. After the other symptoms like a sore throat, fever and headaches occurred, symptomatic treatment was given. Unfortunately, when the real cause was found, the patient could not tolerate the other treatment for ENKL. Outcomes: Since the patient was treated with steroid without improvement, she died due to the septic shock and multiple organ failure. Lessons: Clinicians should always be cautious to ENKL which can be easily be misdiagnosed in the early stage. Early diagnosis and appropriate treatment are keys to raise the survival rate of ENKL patients.